Alaska : An American Colony - Haycox, Stephen W. (Book collections on Project MUSE., 2020)
"Alaska, an American Colony traces Alaska's development from the early postcontact period through Russian America and U.S. territorial status and statehood, including an overview of the region's geography and of Alaska's Native peoples, whose involvement in the state's economic, political, and social life and development continues to this day. In contrast to the stereotype of Alaska as a place where rugged individualists triumph over a harsh environment, distinguished historian Stephen Haycox offers a less romantic, more complex history of Alaska's past and the similarities between Alaska and the American West."--